Incumplimiento de las garantías básicas del debido proceso y el derecho a la seguridad jurídica en el trámite administrativo que ejecuta, la autoridad de salud en la resolución de infracciones de primera instancia - LEÓN MACAS, JULIO CÉSAR (2018)
The present thesis titled, “The non-compliance of the basic warrants of due process and the right to legal security in the administrative process that the health authority executes in the resolution of infractions of first instance”. It carries an existential problem to the understanding for the application to the own warrants that support to the citizens in our country and not reflect a constitutional culture of, respect to the dignity of people and to the human rights, in consequence of that many rights are violated; therefore to the affectation of their rights of the due process, the harmed people are in the necessity to propose protection actions. Inside the investigation it`s planted the general objective pretending to make by conceptual, doctrinal and juridical study, about the violation of the rights and guarantees of the alleged offenders, in the administrative process executed by the Health Authority. In those procedures there is the vulnerability to most of indicted, unrespecting the norms and procedural principles stipulated in our country laws. The first specific objective consists in establish, the warrants of the due process, that are violated by the health authorities in the administrative procedure, It clearly recognizes that values where the health authorities are the ones in charge to administrate the justice in this field, violate the due process in the suppose case to be considered alleged offenders. 5 Therefore, inside the third and last specific object I consider to propose a reform project to the health`s legal regime for the correct application to the warrants of the due process and legal security to the involucrate parts, in administrative procedures in infractions, in front of the health authority. Welcoming to all involucrate people in this type of transgression, and also benefiting the health`s system of justice. As long as the control systems don`t guarantee a due process to suppress to officers or authorities who are responsible and tear up the fundamental principles in the supreme Law and the normative to the Health`s Organic Law, the affectation of their rights in a sanctioning process, It will be continue repetitive for those involucrate people who feel injured and they are in the necessity to propose protection actions, with the purpose their rights. By establishing parameters for conceptual, doctrinal and legal research, the application of surveys and interviews allowed to get views with clear and precise foundations, the most recognized bibliography that contributed to the verification of the objectives and to the contrast of the hypothesis raised referring to this practice; where the Constitution of the Ecuador Republic, supports all people in any process.